Effect of early skin-to-skin contact on breast-feeding. (October 2013) - Suzuki, S.
<x xml:space="preserve">Abstract</x> We examined the effect of early skin-to-skin contact (SSC) on breast-feeding at 1 month after delivery, in Japanese women. We reviewed the obstetric records of healthy nulliparous women with vaginal singleton delivery at 37–41 weeks' gestation, at the Japanese Red Cross Katsushika Maternity Hospital and between 1 February and 30 November 2011, there was a total of 403 women who planned to breast-feed their babies at birth. Of these, 272 women (67.5%) initiated early SSC in the delivery room and 131 women (32.5%) did not initiate early SSC. There were no significant differences in the obstetric characteristics and birth outcomes between the two groups of women with and without initiating early SSC. However, the rate of exclusive breast-feeding at 1 month after delivery in the group of women following early SSC (59.6%, 162/272) was significantly higher than that in the group of women without early SSC (45.8%, 60/131; crude OR 1.74, 95% CI 1.1–2.7, p = 0.009). The current results may support the benefit of early SSC in Japanese women after vaginal delivery.